Studying the fracture surface of brass CuZn37 and aluminum 1100 and their relationship with formability in Single Point Incremental Forming (Fracture and Structural Integrity, 2025)
Single Point Incremental Forming was conducted on Aluminum1100 and Brass CuZn37 to form a hyperbolic truncated pyramid with varying wall angles until the fracture occurs. The formability of the specimens in terms of fracture depth and maximum wall angle was measured; and scanning electron microscopic photography was used to capture the fractured surface of the specimens to perform a fractography analysis. In each specimen's fracture surface, the identification of the voids shape, calculation of the void volume fraction (VVF) and void size, and the classification of the voids have been performed to allow for the identification of the relationship between formability and the microstructure of both materials. Also, the effect of the input parameters on this relationship has been identified. The results showed that when the VVF and the average void size in the fractured surface increase, the formability of the material increases.  And that the optimal SPIF conditions that increase void volume fraction and formability in CuZn37 occur when all input parameters are set to medium levels. For aluminum 1100, the optimal conditions have a low level of feed rate, a high level of tool speed and sheet thickness, and a medium level of tool diameter and step size.
Keywords: SPIF; Fracture surface; Formability; Void Volume Fraction; Void size; Ductile Materials